Social protection as a tool to address slow onset climate events: Emerging issues for research and policy - Mariya Aleksandrova (Deutsches Institut für Entwicklungspolitik (DIE), 2019)
This discussion paper aims to further awareness of opportunities to address loss and damage caused by climate change-related slow onset events (SOEs) through social protection. The analysis is based on a review of interdisciplinary theoretical and empirical literature. The findings suggest that designing comprehensive, climate-responsive social protection strategies can strongly support proactive measures to avoid, minimise and address the complex, long-term impacts of SOEs on human health, livelihoods, poverty and inequality. This entails improving the effectiveness and extending the coverage of existing social protection systems; mainstreaming climate concerns, including risks associated with SOEs, into national social protection frameworks; integrating social protection with broader climate and development policies and strategies; and developing innovative and transformational approaches to social protection. To this end, several issues for research and policy are discussed. Overall, the paper attempts to set the groundwork for an advanced research and policy agenda on social protection and climate change as well as emphasise the need for wider consideration of social protection in global climate change debates. In addition, the study aims to inform the future work of the Executive Committee of the Warsaw International Mechanism for Loss and Damage associated with Climate Change Impacts in the working areas of SOEs and comprehensive risk management approaches.
Keywords: 320